2018
DOI: 10.1080/21663831.2018.1482837
|View full text |Cite
|
Sign up to set email alerts
|

Highlights on advances in SnO2 quantum dots: insights into synthesis strategies, modifications and applications

Abstract: The applications of SnO 2 are benefited from its nanostructure with different sizes and novel morphologies. When the size of nanoparticles reduces to 1-10 nm, the unique physical and chemical properties will make prominent. SnO 2 quantum dots (QDs), a type of zero-dimensional ultrasmall SnO 2 nanomaterials with a size in 1-10 nm, have displayed unique physical and chemical properties, which are different from those of their larger-sized ones. This review summarizes various synthesis strategies of SnO 2 QDs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 151 publications
0
12
0
1
Order By: Relevance
“…22 However, the adopted synthesis approaches are rather time consuming (several hours), and the removal of additives requires the fine control of the whole process, significantly limiting its large-scale fabrication. Differently, the microwave-assisted synthesis, with an alternative energy input source, is a rapid, uniform, and facile technique to obtain SnO 2 QDs, 23,24 which has been widely applied in the field of photocatalysts 25,26 and sensors 27,28 but seldom in photovoltaics. 9,14 Herein, with the utilization of microwave-assisted solution process, we have developed a super rapid synthesis of SnO 2 QDs without adding any additives.…”
Section: ■ Introductionmentioning
confidence: 99%
“…22 However, the adopted synthesis approaches are rather time consuming (several hours), and the removal of additives requires the fine control of the whole process, significantly limiting its large-scale fabrication. Differently, the microwave-assisted synthesis, with an alternative energy input source, is a rapid, uniform, and facile technique to obtain SnO 2 QDs, 23,24 which has been widely applied in the field of photocatalysts 25,26 and sensors 27,28 but seldom in photovoltaics. 9,14 Herein, with the utilization of microwave-assisted solution process, we have developed a super rapid synthesis of SnO 2 QDs without adding any additives.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The quantum size effects appear when the size of the SnO 2 nanoparticles (NPs) is about 1-10 nm [51]. Du et al [52] prepared SnO 2 QDs via a hydrothermal route.…”
Section: Resistive-based Gas Sensorsmentioning
confidence: 99%
“… 16 The two most major obstacles faced by quantum dots preventing the commercialization of many of these applications are their mechanical, thermal, and chemical instability and the lack of viable large-scale production. 17 19 …”
Section: Introductionmentioning
confidence: 99%
“… 18 For example, embedding quantum dots in an amorphous carbon matrix counteracts the aggregation and volume swelling challenges encountered during lithiation in battery applications. 17 Ge et al 20 also embedded CuO quantum dots (1–2 nm) in a silica matrix, which showed improved thermal stability. Further, these amorphous matrices improve wetting and dispersion that are critical to photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%